1996
DOI: 10.1007/bf00833400
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in benzodiazepine receptor binding in a patient with Angelman syndrome detected by iodine-123 iomazenil and single-photon emission tomography

Abstract: A receptor mapping technique using iodine-123 iomazenil and single-photon emission tomography (SPET) was employed to examine benzodiazepine receptor binding in a patient with Angelman syndrome (AS). AS is characterized by developmental delay, seizures, inappropriate laughter and ataxic movement. In this entity there is a cytogenic deletion of the proximal long arm of chromosome 15q11-q13, where the gene encoding the GABAA receptor beta3 subunit (GABRB3) is located. Since the benzodiazepine receptor is construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…The locus of these motor abnormalities is currently unknown, but it is possible that cerebellar dysfunction is a causal factor, given that ataxia and tremor are both common symptoms of cerebellar disorders. In support of this hypothesis, GABA A receptors have been shown to be reduced in the cerebellum of patients with AS and in postmortem AS material (3)(4)(5). Furthermore, movement studies in patients with AS showed abnormal electromyographic (EMG) rhythmic bursts when maintaining posture (6), which could be indicative of cerebellar dysfunction.…”
Section: Introductionmentioning
confidence: 87%
“…The locus of these motor abnormalities is currently unknown, but it is possible that cerebellar dysfunction is a causal factor, given that ataxia and tremor are both common symptoms of cerebellar disorders. In support of this hypothesis, GABA A receptors have been shown to be reduced in the cerebellum of patients with AS and in postmortem AS material (3)(4)(5). Furthermore, movement studies in patients with AS showed abnormal electromyographic (EMG) rhythmic bursts when maintaining posture (6), which could be indicative of cerebellar dysfunction.…”
Section: Introductionmentioning
confidence: 87%
“…For example, the gabrb3 gene knock-out mice exhibit a cleft-palate in ϳ57% of the homozygous gabrb3Ϫ/Ϫ mice, and (Williams et al, 1995). Another comparative feature is provided by a report involving single photon emission computed tomography (SPEC T) in which a reduction of 22-28% in binding of the benzodiazepine [ 123 I]iomazenil in the frontal and temporal cortex of a 27-yr-old female AS patient was measured (Odano et al, 1996). A similar reduction was observed in the gabrb3 knock-out mice, in which binding of the benzodiazepine ligand [ 3 H]Ro15-4513 was reduced by ϳ45% in whole-brain homogenates of adult (12 weeks) gabrb3Ϫ/Ϫ mice as compared with gabrb3ϩ/ϩ mice (Homanics et al, 1997).…”
Section: Both As Patients and Gabrb3 Gene Knock-out Mice Exhibit Poormentioning
confidence: 99%
“…A postmortem study revealed unchanged GABA levels in the cerebral cortex of an individual with Angelman syndrome as compared with control tissues [15]. Analysis of GABA A benzodiazepine receptor binding by positron emission tomography scanning of individuals with Angelman syndrome has produced divergent results, indicating either decreased [11, 22] or increased [1] binding levels. Finally, a decrease in GABA A β 3 subunit mRNA and protein expression in Angelman cortex has been reported, although expression of other GABA A receptor subunits and functional consequences of this reduction were not determined [10, 29].…”
Section: Introductionmentioning
confidence: 99%